4<span>(9<span>a2</span>−6a+1<span>)
Answer:</span></span>4<span><span><span>(3a−1)</span>2</span><span>4<span><span>(3a-1)</span>2</span></span></span>
Answer:
The answer is 3 , 1 , 2 .
Step-by-step explanation:
I will give an example.
e.g.
x² + 3x + 2
Step 3 :
Set the equation equal to zero :
x² + 3x + 2 = 0
Step 1 :
Completely factor the equation :
x² + x + 2x + 2 = 0
x(x+1) + 2(x+1) = 0
(x+2)(x+1) = 0
Step 2 :
Set each factor equal zero and then solve for the variable :
(x+2)(x+1) = 0
x + 2 = 0
x = -2
x + 1 = 0
x = -1
Answer:
32
Step-by-step explanation:
1/3x96= 31.999
(4x-3)(2x+1) expand the brackets: 8x^2 -2x -3 = area